CENTRAL INLAND FISHERIES RESEARCH STATION, CALCUTTA—ITS ORIGIN, ORGANISATION AND FUNCTIONS - Mandapam, Central Marine Fisheries Research Statio (Indian Journal of Fisheries, 2016)
WITH the growing food scarcity in the country both during and after World War IT, fish-farming assumed importance and urgency. There was immediate need for harnessing all cultivable waters in the country for food production. But as the fundamentals of practical fish-farming as a science and an industry were inadequately known in the country, there was urgent need for organising fishery research on an all-India basis. The Ministry of Agriculture of the Government of India therefore sanctioned an interim scheme, which later covered a five-year period, for research on inland fishery problems.